Diversity and evolution of macrohabitat use, body size and morphology in a monophyletic group of Neotropical pitvipers (Bothrops) - Martins, M.; Araujo, M. S.; Sawaya, R. J.; Nunes, R. (Cambridge University Press, 2001)
The Neotropical pitviper genus Bothrops comprises about 40 species, which occur in all main ecosystems of cis-Andean South America. We explored the relationships of body size and form (tail length and stoutness) with macrohabitat use in 20 forms of Bothrops. Sen-ii-arboreal habits appeared only in forest forms. Semi-arboreals are significantly more slender and have longer tails than terrestrials; body size is not significantly different between terrestrials and semi-arboreals. Within Bothrops, independent contrasts for macrohabitat use were significantly correlated with contrasts of tail size (positively) and stoutness (negatively); thus, the more arboreal the species, the longer its tail and the more slender its body. Contrasts of adult body size seems to remain constant over the lower range of macrohabitat use, but to decrease in species of Bothrops which are more arboreal. Reconstructions of character states indicate that: (1) the ancestor of Bothrops was a small, stout, terrestrial species; (2) semi-arboreal habits appeared one to three times in the genus; (3) a decrease in stoutness and an increase in tail length occurred along with an increase in arboreality in some clades. Although macrohabitat use seems to be important in determining body form in Bothrops, our results also indicate that tail size, stoutness and body size may also be affected by selective agents other than macrohabitat use. The selective agents responsible for the shifts in macrohabitat use in Bothrops are still uncertain, although they may have included prey availability and/or predation pressure. The plasticity of macrohabitat use, morphology and body size described in this study may have been key features that facilitated the highly successful ecological diversification of Bothrops in South America.
Keywords: serpentes; Viperidae; ecomorphology; macrohabitat